Bosnia and Herzegovina : First Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2003)
This paper assesses Bosnia and Herzegovina's First Review Under the Stand-By Arrangement and a Request for Waiver of Performance Criteria. Good progress has been made under the program. Economic activity and fiscal consolidation have exceeded expectations, inflation is low, and fiscal and structural reforms proceed apace. GDP is expected to grow 4 percent in 2002, up from the programmed 2u percent, reflecting strengthened industrial activity and good harvests, buoyed by booming bank credit to households.